Presence of human papillomavirus in breast cancer and its association with clinical features - Galvez, M (2018)
Breast cancer (BC) is the most common cancer and leading cause of cancer-related deaths. Recent evidence indicates that a substantial proportion of BC may be caused by viral infections. The presence of high-risk genotypes of human papillomavirus (HPV) has been demostrated in BC and associated with hispotathological features. The aims of this study were to evaluate the prevalence rate of high-risk HPV DNA in BC and clinical features associated to it.